(untitled) (Med Phoenix, 2021)
Posterior reversible encephalopathy syndrome is a condition occurring in majority of case of hypertensive encephalopathy mainly due to vasogenic edema in parieto occipital region in neuroimaging. It is reversible if timely treatment is done .Here we are reporting a 11 year old female child with acute post streptococal glomerulonephrtitis leading to typical clinical and radiological features of posterior reversible encephalopathy syndrome